Can Tax Avoidance Improve The Positive Relationship Between Intellectual Capital And Firm Value? - Aji, Anggit Kuncoro; Hidayatullah, Firda; Firmansyah, Amrie (Educoretax, 2024)
This study examines the effect of intellectual capital on firm value with tax avoidance as moderation in health sector companies listed on the Indonesia Stock Exchange during the COVID-19 pandemic. CTTOR is employed to find the level of tax avoidance, VAIC is used to find the value of intellectual capital, and Tobin's Q is used to find the firm value. The data used is company financial statement data from 2020 to 2022 using multiple linear regression analysis methods. The type of data is cross-section data and ordinary least squares (OLS) estimation technique. The sample was determined using a purposive sampling technique with a total research sample of 43 data. This study concluded that intellectual capital does not affect firm value. However, after moderation with tax avoidance, the interaction between intellectual capital and tax avoidance has a negative effect on firm value. Therefore, tax avoidance can moderate the effect of intellectual capital on firm value by reducing the negative effect of intellectual capital on firm value during the COVID-19 pandemic. The results of this study can be additional information for the Indonesian Capital Market Supervisory Authority (OJK) and the Tax Authority (DGT) in making rules regarding tax avoidance. OJK can also make policies regarding reporting the company's intellectual capital in one account to make it easier for novice investors to understand. DGT can utilize this research to evaluate corporate tax avoidance.